Tailoring fungal morphology of Aspergillus niger MYA 135 by altering the hyphal morphology and the conidia adhesion capacity: biotechnological applications - Colin, Veronica Leticia (2013)
Current problems of filamentous fungi fermentations and their further successful developments as microbial cell factories are dependent on control fungal morphology. In this connection, this work explored new experimental procedures in order to quantitatively check the potential of some culture conditions to induce a determined fungal morphology by altering both hyphal morphology and conidia adhesion capacity. The capacity of environmental conditions to modify hyphal morphology was evaluated by examining the influence of some culture conditions on the cell wall lytic potential of Aspergillus niger MYA 135. The relative value of the cell wall lytic potential was determined by measuring a cell wall lytic enzyme activity such as the mycelium-bound β-N-acetyl-Dglucosaminidase (Mb-NAGase). On the other hand, the quantitative value of conidia adhesion was considered as an index of its aggregation capacity. Concerning microscopic morphology, a highly negative correlation between the hyphal growth unit length (lHGU) and the specific Mb-NAGase activity was found (r = −0.915, P < 0.001). In fact, the environment was able to induce highly branched mycelia only under those culture conditions compatible with specific Mb-NAGase values equal to or higher than 190 U gdry.wt -1. Concerning macroscopic morphology, a low conidia adhesion capacity was followed by a dispersed mycelial growth. In fact, this study showed that conidia adhesion units per ml equal to or higher than 0.50 were necessary to afford pellets formation. In addition, it was also observed that once the pellet was formed the lHGU had an important influence on its final diameter. Finally, the biotechnological significance of such results was discussed as well.